Música na IECLB: dialogando sobre a prática musical na Comunidade Evangélica Luterana Scharlau e teologia de Lutero - Ferreira, Dieison Gross (2015)
This research has the general objective investigate the theological roots of hymns and sacred songs sung in the Evangelical Lutheran Community Scharlau, IECLB to thus understand theology from this context, its specific objectives are to examine the history of IECLB , the Encontrão Movement and the Evangelical Lutheran Community Scharlau , his contributions to the development of community music and verify to what extent is the influence of theological currents in the definition of the chosen hymn books and music, investigate the extent to which theological and musical conceptions of Luther are present in contemporary music sung in the Evangelical Lutheran Community Scharlau and delimit, from the analysis of modernity and postmodernity in relation Luther's theology , criteria of possibilities for the choices of songs to be sung in the celebrations. To support the research , we used various references such as books , newspapers, magazines , minutes , hymnals and songbooks . The composition of the hymnal of the Evangelical Lutheran Community Scharlau is analyzed by checking the songs are of other faiths from the Lutheran theology and Encontrão Movement. The results of the research allowed to observe how to set up the history of IECLB and his music, as Luther had appreciation for music and his concern for the care of the music, and how the selection criteria for the formation of hymnals and songbooks may feature a theology music community.